1999
DOI: 10.1016/s0008-6363(98)00255-7
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte recruitment in rupture prone regions of lipid-rich plaques: a prominent role for neovascularization?

Abstract: Neovascularisation and expression of adhesion molecules by microvessels at sites of vulnerable lipid-rich plaques may sustain the influx of inflammatory cells and hence, could contribute to plaque destabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
0
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(157 citation statements)
references
References 14 publications
5
149
0
3
Order By: Relevance
“…22,23 Previous reports have studied plaque neovascularization in advanced atherosclerosis in carotid endarterectomy specimens. 24,25 However, these studies did not evaluate neovascularization across the vessel wall. Our study in aortic sections identified neovessel density within the plaque to be lower than that within the tunica media.…”
Section: Moreno Et Al Neovessels and Plaque Rupture 2035mentioning
confidence: 99%
“…22,23 Previous reports have studied plaque neovascularization in advanced atherosclerosis in carotid endarterectomy specimens. 24,25 However, these studies did not evaluate neovascularization across the vessel wall. Our study in aortic sections identified neovessel density within the plaque to be lower than that within the tunica media.…”
Section: Moreno Et Al Neovessels and Plaque Rupture 2035mentioning
confidence: 99%
“…22 The pivotal work of O'Brien et al 23,24 documented the mechanisms underlying neovessel recruitment of plaque leukocytes in human atherosclerosis. The expression of vascular cell adhesion molecule-1, intercellular adhesion molecule-1, and E-selectin were 2-to 3-fold higher on neovessels than on arterial luminal endothelium, confirming the predominant role for neovessels as a pathway for leukocyte infiltration in human coronary plaques.…”
Section: Neovascularization and Leukocyte Recruitmentmentioning
confidence: 99%
“…13,14 Thus, the neovessels in atherosclerotic plaques express leukocyte adhesion molecules and are therefore able to sustain the influx of leukocytes into the plaque. 28 Importantly, the neovessels may also act as a port of entry for circulating MC progenitors to the deep areas of the plaques. In addition, rupture of the fragile walls of the neovessels may allow erythrocytes to leak into the plaque.…”
Section: Lappalainen Et Al Bfgf In Mast Cells In Human Coronary Arteriesmentioning
confidence: 99%